Application of Hybrid Transform Domain Digital Watermarking in Power System Information Security - Shaomin Zhu; Zhiqiang Zhang (Dianxin kexue)
With the rapid development of electric power information industry, a lot of multimedia products such as digital image, audio, video and three dimensional models were produced and applied during the electric power process of the production, operation and management. Therefore, how to realize digital media security effectively is becoming a challenging problem. A new image watermarking algorithm in hybrid transform domain was proposed. The secret watermark information bits were embedded into low frequency subband in hybrid transform. According to energy distribution and visual masking in low frequency subband, the singular values of the selected low frequency subband blocks were adaptively applied quantization index modulation for embedding watermark information. Experimental results show that the algorithm has good image vision fidelity. The proposed digital watermarking is playing a more important role in network security for electric power system.